Zona sur: Urdimbres de la acción colectiva popular en el Gran Buenos Aires (1974-1989) - Pinedo, Jerónimo (Entre los libros de la buena memoria, 2022)
Southern Zone. Warps of Popular Collective Action in Greater Buenos Aires (1974-1989): Popular politics, in its intricate folds and retreats, builds spaces and spreads its sediments. This book seeks to unravel the warp and woof of popular collective action in the southern zone of Greater Buenos Aires between 1974 and 1989. The unearthing of the contentious life of popular classes and a detailed reconstruction of the episodes that mark it will allow readers to go through a spatio-temporal weave in which territories and senses of place are created and recreated. Thus, the place emerges as an intrinsic part of the socio-historical processes, as a factor that intervenes in the dynamics of struggle, and as its provisional result. Situated at a threshold of social, economic and political changes in Argentina, the episodes narrated here, based on documentary archives and memorial records, describe a historical geography of popular struggles in a crucial period of Argentina's recent history.